Exploring the socio-emotional experiences of adults with cerebral palsy in a residential care facility in Johannesburg, South Africa - Tsiane, Dimpho (My University, 2017)
There has been much written on the biomedical concerns of cerebral palsy, yet there has been very little researched or reported on the socio-emotional aspects of cerebral palsy in a residential care facility. This study aimed to explore the socio-emotional experiences of adults with cerebral palsy in a residential care facility. The study made use of an exploratory qualitative design and employed semi-structured interviews with a purposive sample of 10 cerebral palsied adults. Some important findings that emerged from a thematic qualitative analysis of the data included being overwhelmed by the new environment; feelings of freedom, happiness and independence; support from various role players; age and communication challenges; and residents accepting circumstances and remaining positive. The main conclusion drawn from the study was that despite the challenges the residents faced, they were resilient enough to employ coping methods that assisted them through the process. Key words: cerebral palsy, socio-emotional, transitioning, residential care facility
In partial fulfilment of the requirements For the Degree Bachelor of Social Work